2009
DOI: 10.1021/ma8028562
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Dependent Kinetics of Cu(0)-Wire-Catalyzed Single-Electron Transfer Living Radical Polymerization of Methyl Acrylate in DMSO at 25 °C

Abstract: The effect of Cu(0) wire dimensions on the Cu(0) wire/Me 6 -TREN-catalyzed heterogeneous singleelectron transfer living radical polymerization (SET-LRP) of methyl acrylate (MA) initiated with methyl 2-bromopropionate (MBP) in DMSO at 25 °C was analyzed by kinetic experiments. These kinetic results were compared with those of Cu(0) powder/Me 6 -TREN-catalyzed SET-LRP. Both wire and powder produce perfect SET-LRP with a first-order rate of polymerization in growing species up to 100% conversion. Nevertheless, Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
281
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 254 publications
(291 citation statements)
references
References 54 publications
9
281
0
Order By: Relevance
“…3 Subsequently, SET-LRP was expanded to acrylates, [4][5][6][7][8][9][10][11][12][13][14][15][16][17] methacrylates, 8,[18][19][20][21][22][23][24][25] acrylamides, [26][27][28][29][30][31] methacrylamide, 32 acrylonitrile, 33,34 and monomers containing more complex water soluble side groups, such as sugars, 35,36 N-(2-hydroxypropyl) methacrylamide, 32 dimethylacrylamide, 26 N-isopropylacrylamide, 26,[37][38][39] oligo(ethylene oxide) methyl ether acrylate, 40 oligo(ethylene oxide) methyl ether methacrylate, 41 hydroxyethyl acrylate, 10 hydroxyethyl methacrylate 23 and acryloyl morpholine. 42 At the same time as these developments, the list of solvents used in SET-LRP was expanded to other solvents that in combination with aliphatic N-donor ligands, such as tris[(2-dimethylaminoethyl)...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Subsequently, SET-LRP was expanded to acrylates, [4][5][6][7][8][9][10][11][12][13][14][15][16][17] methacrylates, 8,[18][19][20][21][22][23][24][25] acrylamides, [26][27][28][29][30][31] methacrylamide, 32 acrylonitrile, 33,34 and monomers containing more complex water soluble side groups, such as sugars, 35,36 N-(2-hydroxypropyl) methacrylamide, 32 dimethylacrylamide, 26 N-isopropylacrylamide, 26,[37][38][39] oligo(ethylene oxide) methyl ether acrylate, 40 oligo(ethylene oxide) methyl ether methacrylate, 41 hydroxyethyl acrylate, 10 hydroxyethyl methacrylate 23 and acryloyl morpholine. 42 At the same time as these developments, the list of solvents used in SET-LRP was expanded to other solvents that in combination with aliphatic N-donor ligands, such as tris[(2-dimethylaminoethyl)...…”
Section: Introductionmentioning
confidence: 99%
“…10 42 exhibit amplified adsorption and desorption processes that may complement the previous studies on the elucidation of the role of the surface of Cu(0) catalyst on the activation and deactivation steps of SET-LRP. 11,[58][59][60][61] This publication reports the aqueous SET-LRP of HEA and OEOMEA mediated by "in situ" generated Cu(0) catalyst. 26,37,38 The study reported here demonstrates that the surface of Cu(0) is responsible both for the activation of the initiator and dormant growing species, as well as for the much lower extent of bimolecular termination observed during polymer synthesis by SET-LRP.…”
Section: Introductionmentioning
confidence: 99%
“…44,45 In addition, none of the aforementioned reports, including Cu(0)-mediated RDRP have been employed for the synthesis of PDMAEA star homo and block copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…17,61,62 More recently, Percec and co-workers proposed that the Cu(0)-based living radical polymerization proceeds via a single-electron transfer mechanism under certain conditions and that their systems are highly effective for the very fast living radical polymerization of various monomers, leading to well-controlled high-molecular weight polymers with narrow MWDs. [63][64][65][66] In contrast, the Cu(I)-based systems in the presence of reducing agents, such as tin(II) 2-ethylhexanoate, ascorbic acid, Cu(0) and radical initiators, also induced an efficient living radical polymerization, in which the accumulated Cu(II) species changed into the active Cu(I) species via the reduction by these additives. [67][68][69][70] Although the working mechanisms of Cu(0) are still controversial and may depend on the conditions, it is clear that the use of lower oxidation metal species is important for constructing highly catalytic systems.…”
Section: Metal Catalytic Systemsmentioning
confidence: 99%